The Impact of Strategic Planning on Organizational Performance: The Case of Public Organization in Qatar - Maharmeh, Thmer Mohammed (Journal of Economic, Administrative and Legal Sciences, 2020)
The main objective of the research is to investigate the degree of effects of strategic planning and its dimensions (vision and mission, strategic objectives and values, projects and operational plans, and follow-ups and control) on organizational performance. Data was collected by using a closed-ended survey from simple random sample of employees. Data were analyzed by using suitable descriptive and analytical statistical methods available at SPSS. Results of data analysis revealed that there is strong and positive relationship between strategic planning and organizational performance. It was found that organizational performance is greatly influenced by strategic planning. Based on that, it was recommended to support strategic planning in public organizations.
Keywords: strategic planning; institutional performance; government organizations